2004
DOI: 10.1074/jbc.m312951200
|View full text |Cite
|
Sign up to set email alerts
|

Modified Heparin Inhibits P-selectin-mediated Cell Adhesion of Human Colon Carcinoma Cells to Immobilized Platelets under Dynamic Flow Conditions

Abstract: Accumulating evidence indicates that the formation of tumor cell platelet emboli complexes in the blood stream is a very important step during metastases and that the anti-metastasis effects of heparin are partially due to a blockade of P-selectin on platelets. In this study, heparin and chemically modified heparins were tested as inhibitors of three human colon carcinoma cell lines (COLO320, LS174T, and CW-2) binding to P-selectin, adhering to CHO cells expressing a transfected human P-selectin cDNA, and adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 38 publications
3
58
0
Order By: Relevance
“…In the assay of enzyme treatments, A375 cells (10 7 cells/ml in IMDM) were simultaneously treated with 5 U/ml heparinases I, II and III in the presence of a mixture of protease inhibitors (10 mg/ ml leupeptin, 20 mg/ml aprotinin and 10 mM benzamidine) for 1 h at 37°C with end-to-end rotation. 17 …”
Section: Cell Adhesion Assay In Static Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the assay of enzyme treatments, A375 cells (10 7 cells/ml in IMDM) were simultaneously treated with 5 U/ml heparinases I, II and III in the presence of a mixture of protease inhibitors (10 mg/ ml leupeptin, 20 mg/ml aprotinin and 10 mM benzamidine) for 1 h at 37°C with end-to-end rotation. 17 …”
Section: Cell Adhesion Assay In Static Conditionmentioning
confidence: 99%
“…17 Briefly, the bottom of the chamber was a 35-mm tissue culture dish precoated with GP-CHO (or CHO) cells over night, or a 35-mm circular glass slide (treated with 4% APES) precoated with PRP (platelet was adjusted to 2 3 10 8 /ml) for 60 min at 37°C. To induce a IIb b 3 activation, GP-CHO cells were stimulated with 10 mM DTT for 20 min at 22°C, the glass slides coated with platelets were incubated with thrombin (1 U/ml, sigma) for 10 min at 37°C.…”
Section: Cell Adhesion Assay Under Flow Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heparin has weak inhibitory activity against platelet-collagen interactions which accounted for its non-specific interference with agonist-receptor interactions (Davies and Menys 1982). Some chemically modified heparins with low anticoagulant activities may also have potential value as therapeutic agents that block P-selectin-mediated cell adhesion (Wei et al 2004). In this study, we found that heparin directly inhibited platelet adhering to endothelial cells.…”
Section: Discussionmentioning
confidence: 67%
“…[99] Astenose Adjuvant in cardiovascular intervention c [113] ROH Heparanase antiangiogenesis inhibitor b [114] ROH P selectin inhibitor [115] LAC-HP antimetastatic b [116] ROH Integrin-melanoma cell binding inhibitor a [117] ROH Antianemic as hepicdine inhibitor b [118] ROH Antinflammation-human elastase inhibitors a [118] gs-LMWH ORG 31733 HIV-1 and HIV-2 inhibitor a [120] SR 80258 Allergic airway response inhibitor b [121] Vasoflux Anticoagulant independent from AT activity, coadjuvant in myocardial infarction therapy d [108,109] NAC from Tinzaparin Antimetastatic b [122] gs-LMWH antimalarial, parasite adhesion, inhibitor b [44] DF01 -Tafoxiparin Labor pain attenuation d [111] M-402 Nocuparanib Metastasis and multiple pathway inhibitor d [110] DFX 232-Sevuparin Antimalarial, distrupting "Plasmodium falciparium" rosettes d [112]]-Preventive activity of vasoocclusion in sickle severe hereditary anemia d S-NACH Anticancer increasing tumor chemo-responsiveness c [35] gs-ULMWH RO-Fondaparinux Antinflammation b [123] Undersulfated RO ST1514" Antinflammatory -heparanase inhibitor b [124] Antiangiogenic, as FGF-2 and VEGF inhibitors b [125,126] N-acylated gs-heparins …”
Section: Conflict Of Interest Statementmentioning
confidence: 99%